Assessing Student Leaders' Leadership Styles and Conflict Management - Ma Leah Ulanday; Lemellu Nida L Samiento; Cereneo jr. S Santiago; Zarah Jane R Centerno (Universidade Estadual de Alagoas, 2024)
Student leadership gives students the training they need to engage themselves in school-related tasks or concepts, objectives, and aspirations beneficially and constructively. It teaches them how and when to plan an event, manage their schedule, improve their speaking abilities, and lead students. To achieve a target, leadership is a flexible process that calls for collaboration with others in both academic and professional lives. For individuals who are expanding their professional competencies, gaining leadership skills is essential. To enable students to learn their attributes and better prepare them for their careers, leadership qualities and skills should be measured. This study examined the profile in terms of age and sex, leadership styles, and conflict management of student leaders in a state university. A descriptive-correlation research design was employed in the study with undergraduate student leaders of their respective department organizations who enrolled in different courses. (N=70). Results show that majority of student leaders age is between 18- 21 and are dominated by male student leaders. It can also be gleaned that the majority of student leaders possess a democratic leadership style. Democratic leadership approaches have provided leaders the capability of making wise decisions, collaborating with others, and asking pertinent questions to people to handle certain issues. In terms of conflict management, the number one conflict management strategy used by the leaders is accommodating strategy Moreover, there is no significant relationship between the leadership style of student leaders and conflict management. Regardless of the leadership style of student leaders, it is up to them how they will handle conflict management effectively. Student leaders set the tone for conflict management through their leadership styles.